Strategi Pemasaran Benih Ikan Lele Sangkuriang (Gariepinu Var) di Desa Tawamelewe Kecamtan Uepai Kabupaten Konawe : ( Studi Kasus : UPR Nengah Surya Mina ) - Arif Charya; Sarty Syarbiah; I Made Sukratman (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2024)
This study aims to determine the marketing strategy of sangkuriang catfish seeds (Clarias gariepinu var) in Tawamelewe Village, Uepai District, Konawe Regency using SWOT analysis. The respondents in this study were the owner of a catfish hatchery, Mr. Nengah Sama. The results of the analysis of the sangkuriang catfish hatchery business began in 2013 with a pond area of ​​20 ares, until now in 2024 with a pond area of ​​2 ha. The business capital is IDR 3,000,000-5,000,000. up to the current capital of IDR 30,000,000.-50,000,000. The monthly income of UPR Nengah Surya mina reaches IDR 6,000,000.- IDR 8,000,000. if demand is high, the monthly income reaches IDR 8,000,000.- IDR 10,000,000. The results of internal and external factors, the strength factor of the Sangkuriang Catfish Seedling Business in Tawamelewe Village, Uepai District is superior compared to its weaknesses. The opportunity factor in the current condition is quite large compared to its threats. The Sangkuriang Catfish Seedling Business in Tawamelewe Village, Uepai District is currently in Quadrant I, a company that is in quadrant I is a very profitable situation. The company has opportunities and strengths so that it can take advantage of existing opportunities. The strategy that can be done is by supporting aggressive business growth.